IMPROVING THE LEARNING OUTCOMES OF GRADE V STUDENTS IN SCIENCE THROUGH ELEMENTARY SCHOOL SCIENCE KIT MEDIA - Sianturi, Septriyanti Sianturi; syamsuyurnita, Syamsuyurnita; Siregar, Silsia Risqha revolina (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
This study is a classroom action research to improve students' IPAS learning outcomes about sound and its properties through science kits. Science kits are didactic tools used in science learning and include whips, whips, funnels, balances, and others. This research was conducted in 2 cycles and pre-cycle, and each cycle consisted of 2 meetings. This PTK research consists of 4 stages, namely the planning stage, the implementation stage, the observation stage, the evaluation and reflection stage. This research was conducted in the odd semester of the 2024/2025 school year. The sample of this study included all 5th-grade students of SD Negeri 066054 Medan, totaling 23 people. The research data were collected through observation and tests. The tests used in this study consisted of 5 multiple-choice questions and 5 description questions. This research was described quantitatively and qualitatively. The data were analyzed using N-gain with 70% completeness criteria according to KKTP. The results of this study indicate that student learning outcomes have increased. In cycle I there was an increase of 36%, while in cycle II there was an increase of 48%, and all students it